2012
DOI: 10.1371/journal.pone.0049152
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Activation Inhibits VLDL Production and Reverses Hepatic Steatosis by Decreasing Hepatic Lipogenesis in High-Fat-Fed APOE*3-Leiden Mice

Abstract: ObjectiveIn addition to improve glucose intolerance, recent studies suggest that glucagon-like peptide-1 (GLP-1) receptor agonism also decreases triglyceride (TG) levels. The aim of this study was to evaluate the effect of GLP-1 receptor agonism on very-low-density lipoprotein (VLDL)-TG production and liver TG metabolism.Experimental ApproachThe GLP-1 peptide analogues CNTO3649 and exendin-4 were continuously administered subcutaneously to high fat diet-fed APOE*3-Leiden transgenic mice. After 4 weeks, hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 45 publications
9
69
1
Order By: Relevance
“…Rats with chronically elevated plasma GLP-1 levels showed decreased expression of lipogenic enzymes and reduced hepatic TG content ( 37 ). In line with this, continuous subcutaneous infusion of exendin-4, a GLP-1 receptor agonist, decreased hepatic VLDL-TG production in mice ( 8 ). Importantly, also central GLP-1 infusion decreased hepatic TG content and expression of lipogenic enzymes in mice, suggesting that GLP-1 can at least in part affect hepatic TG metabolism via a central mechanism ( 38,39 ).…”
Section: Anatomy Of Hypothalamic Sympathetic Outflowmentioning
confidence: 60%
“…Rats with chronically elevated plasma GLP-1 levels showed decreased expression of lipogenic enzymes and reduced hepatic TG content ( 37 ). In line with this, continuous subcutaneous infusion of exendin-4, a GLP-1 receptor agonist, decreased hepatic VLDL-TG production in mice ( 8 ). Importantly, also central GLP-1 infusion decreased hepatic TG content and expression of lipogenic enzymes in mice, suggesting that GLP-1 can at least in part affect hepatic TG metabolism via a central mechanism ( 38,39 ).…”
Section: Anatomy Of Hypothalamic Sympathetic Outflowmentioning
confidence: 60%
“…Exendin-4 as a GLP-1 receptor agonist can decrease LDL, apolipoprotein B, TG, and increase HDL. Research by Parlevliet et al [18] indicated that this drug could reduce hepatic steatosis and ameliorate dyslipidemia by decreasing serum levels of VLDL and TG. The corresponding results are in agreement with the present study showing that exendin-4 can reduce harmful lipid factors and increase the serum level of HDL.
Figure 2.Treatment of NMRI mice with exendin-4 altered hepatic lipid and enzymatic profiles in the serum.
…”
Section: Resultsmentioning
confidence: 99%
“…Although chronic administration of GLP-1R agonists in rodent models of dyslipidemia also reduces the levels of circulating lipoproteins, whether these findings reflect direct or indirect actions on liver, intestine, or other tissues remains unclear. 48,49 Furthermore, the specific GLP-1R + cell types mediating these effects on intestinal and hepatic lipoprotein metabolism require further elucidation. Because intracerebroventricular exendin-4 administration (0.023 or 0.23 nmol) reduced hepatic TAG secretion after an overnight fast in C57BL/6 mice fed a high-fat diet for 4 weeks, 7 and acute intracerebroventricular GLP-1 administration rapidly lowered hepatic TAG content in hyperinsulinemic mice fed a high-fat diet, 50 the importance of central GLP-1R signaling for the control of lipid metabolism requires further investigation.…”
Section: Preclinical Studiesmentioning
confidence: 99%